1992
DOI: 10.1021/j100204a019
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of pulsed laser evaporated gallium and indium atoms with molecular oxygen: matrix infrared spectra of new gallium dioxide and indium dioxide species

Abstract: Infrared spectra were obtained in solid argon at 12 * 1 K for gallium and indium oxides produced from the reaction of laser-ablated metal atoms with molecular oxygen. Several new molecules were characterized including bent species Ga0; at 568.7 cm-' and InO; at 462.4 cm-', which were distinctly different from previously observed cyclic M 0 2 species, linear metal atom insertion products OGaO at 912.7 cm-' and OInO at 755.4 cm-', and linear GaOGaO at 967-959 cm-' and InOInO at 816.6 cm-'. The linear insertion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 9 publications
10
71
0
Order By: Relevance
“…6 (2) Reaction 2 is essentially isoergic, and some activation energy is required. They exhibit virtually the same H/D ratio as AlH, and the A1D counterparts do not agree with the spectrum of D2O in solid arg0n.1~ (The H/D ratios for water AlHz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 (2) Reaction 2 is essentially isoergic, and some activation energy is required. They exhibit virtually the same H/D ratio as AlH, and the A1D counterparts do not agree with the spectrum of D2O in solid arg0n.1~ (The H/D ratios for water AlHz.…”
Section: Discussionmentioning
confidence: 99%
“…Al, + H, -HAlAlH (6) Pulsed-Laser Ablation. The laser power densities employed here ((1-10) X lo9 W/cm-2) are higher than used in earlier studies where hyperthermal velocities corresponding to kinetic energies in the 2-4-eV range were measured.…”
Section: E'mentioning
confidence: 99%
See 1 more Smart Citation
“…Several interesting products were recently observed from the reactions of pulsed laser evaporated B, AI, Ga, and In atoms with oxygen [1]. These group 13 oxides, exhibiting different stoichiometries, are remarkably structure rich.…”
Section: Introductionmentioning
confidence: 99%
“…9 Small clusters of gallium oxide can be considered a prototype model to understand the physics and chemistry of nanostructures. A few scattered studies have been reported on gallium oxide at the cluster level including monomer, 10,11 triatomic, 12,13 and dimer [14][15][16][17] clusters. Recently, we initiated a systematic study of the evolution of the physical and chemical properties of small gallium oxide clusters to determine their convergence to the corresponding bulk values.…”
Section: Introductionmentioning
confidence: 99%